Prevalence and risk factors for medical events following exercise at Australian Greyhound race meetings. Issue 4 (25th March 2018) - Karamatic, SL; Anderson, GA; Parry, BW; Slocombe, RF; Mansfield, CS
Abstract : Aim: A prospective, observational study to determine the prevalence of post‐exercise conditions at Australian Greyhound race meetings and to assess association with race performance and other environmental, race‐ and dog‐related factors was undertaken. Methods: A total of 4020 starters were observed (2813 Greyhounds, 1009 trainers, 536 races, 52 race meets, 48 race dates and 11 race tracks) following a race. The presence of diaphragmatic flutter (DF), ataxia, seizure, collapse or sudden death was recorded. Risk factors were screened by univariable logistic regression prior to multivariable backward stepwise model building. Results: In this study, 962 starters (n = 768 dogs) had DF (23.9%), 16 starters were ataxic (0.4%) and there were no observed cases of collapse, seizure or sudden death. Race track location, increasing race distance, race grade based on increasing 1st place prize value, lower (earlier) race number at the meeting, age, a previous observation of DF at the last start, females, colour (white) and better finishing position were all associated with an increased risk of a Greyhound being observed with DF. However, when logistic regression assessing the random effect of dog was performed, the presence of previous DF was not significant. In this cohort, DF was common following strenuous exercise in Greyhounds and on its own does not appear to result in reduced performance or distress to the animal. Conclusion: The incidence of ataxia was low and collapse, seizure and sudden death were not observed. However, even though uncommon, ataxia has welfare concerns for racing Greyhounds that warrants further investigation.